(untitled) (Third Sector Social Economic Review, 2022)
In the study, it was aimed to identify the predictive role of love and respect values over the value of fellowship. The study sample of the research, which was structured in accordance with multifactor predictiive correlational design, consisted of 972 secondary school students studying in Uşak province, Turkey in the 2021-2022 academic year and chosen through simple random sampling method (female=527, male=445). The research data were collected through three separate scales , which are ""Love Scale, Respect Scale, and Fellowship Scale"", developed by author along with conducting validity and reliability studies. In the analysis of the research data, descriptive statistics, Pearson correlation, and multivariate linear regression analysis were used. According to the results of the analysis, it was seen that the participating secondary school students had relatively high values of love, respect, and fellowship, and that these values positively and significantly correlated with each other. In addition, it was determined that love and respect values positively and significantly predicted the value of fellowship, and that they explained approximately 38% of the changes in the value of fellowship. Thus, it was concluded that love and respect are effective values on the value of fellowship, and based on this result, teachers were recommended to benefit from these values in teaching the value of fellowship.